Morphological characteristics of temporal area skin in patients with an additional pathology on age aspect. - Tverdokhlib, I. V.; Makarchuk, O. I. (Морфологія / Morphologia / Morfologìâ, 2015)
Background. Improvement of the technical aspects of surgery in aesthetic surgery led to an increase in the number of transactions and significant increase contingent of women who are turning to specialized clinics. But it also significantly increased the proportion of patients with a variety of concomitant diseases requiring new approaches to operational technologies and special attention in the postoperative period. In this group of patients is high risk of intraoperative and postoperative complications significantly limits the range of indications. So to prevent these complications is an important question when planning operations in aesthetic surgery of the face. Objective. Determine structural and functional changes of temporal area skin in women of different age groups with an additional internal pathology. Methods. Intraoperative biopsy material of skin of 104 women at the age from 19 to 73 years, that was taken during standard surgery instrumentations for different defects of face skin correction, was investigated. Results and conclusion. It was determined, that involutive dynamic of microvessel condition in papillary layer of derma coincides with grade reduction of relative volume of microvessels bed. Microcirculation age changes include structural disorders of intrapapillary capillary loops, disorganization of arterioles in papillary and reticular layers of derma, disorders of venules because of the changes in microenvironmental fibrillar network. It is typical at the patients with nicotinic dependence, ischemic heart disease, hypertonic disease, a diabetes, and also adiposity of a different degree essential infringement of microvessels bed structure criteria of skin condition that gives the basis for allocation of the given contingent of patients as group of high intraoperative and postoperative risk at carrying out of frontlift.